Pengaruh Literasi Keuangan, Fear Of Missing Out Dan Ekspektasi Return Terhadap Minat Investasi Saham Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang Angkatan 2022 - Maziz Rusydani; Ronny Malavia Mardani; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study examines the effect of financial literacy, fear of missing out (FoMO), and return expectation on stock investment interest among students of the Faculty of Economics and Business, Universitas Islam Malang, class of 2022. The research employs a quantitative approach with a survey method. The population consists of FEB UNISMA students from the 2022 cohort enrolled in the Management, Accounting, and Islamic Banking study programs who have received investment-related education through courses such as Digital Investment and the Islamic Capital Market, possess basic investment knowledge, and may or may not have prior investment experience. Simple random sampling was used, resulting in a total of 100 respondents. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 25. The findings reveal that financial literacy, fear of missing out, and return expectation each have a positive and significant influence on students’ interest in stock investment. These results indicate that enhancing financial knowledge, addressing psychological factors, and understanding expected investment returns are crucial in encouraging more rational and sustainable stock investment interest among university students. Keywords: Financial Literacy, Fear Of Missing Out (FoMO), Return Expectation, Stock Investment Interest